COVERAGE AND FACTORS ASSOCIATED WITH HEALTH INSURANCE UTILIZATION AMONG REPRODUCTIVE WOMEN: INSIGHTS FROM TANZANIA DEMOGRAPHIC HEALTH SURVEY 2022. A QUANTITATIVE STUDY. - Ikwara, Emmanuel Asher; Humphrey, Atwijukiire; Ritah, Atuhaire (Student’s Journal of Health Research Africa, 2024)
Background: Universal Health Coverage aims to alleviate poverty caused by out-of-pocket health expenses, affecting 150 million annually, particularly in low- and middle-income countries. Health Insurance plays a crucial role, yet faces challenges like low coverage rates and equity issues. This study aimed to assess the extent of coverage and identify factors influencing the utilization of health insurance among reproductive women in Tanzania, utilizing data from the 2022 Demographic Health Survey. Methods: The study quantitatively examined data from the 2022 Tanzania Demographic and Health Survey, involving 15,254 women of reproductive age. The analysis included univariate, bivariable, and multivariable techniques utilizing chi-square and multilevel logistic regression. Findings reported as adjusted odds ratios (AOR), determined statistical significance at p<0.05. Results: The overall coverage of Health Insurance (HI) stood at a mere 5.7%. Individuals aged 35-49 years were 1.6 times more inclined to utilize insurance compared to those aged 15-24 years (AOR=1.633, 95%CI: 1.326-2.010). Residents in rural areas exhibited a 1.3 times higher likelihood of using HI compared to their urban counterparts (AOR=1.300, 95%CI: 1.086-1.556). Moreover, individuals with a higher level of education were 8 times more inclined to use HI compared to those with no education (AOR=8.113, 95%CI: 5.009-13.141), indicating a correlation between increased educational attainment and HI utilization. Additionally, participants owning a television were 1.4 times more likely to use HI than those without (AOR=1.419, 95%CI: 1.135-1.774). Those who held an account in a bank or financial institution were 3.9 times more likely to utilize insurance compared to those without an account (AOR=3.999, 95%CI=3.302-4.843). Conclusions: The extent of Health Insurance (HI) coverage in Tanzania continues to fall short, impeding advancements toward universal health coverage. Recommendation: The study recommends bolstering public awareness initiatives to underscore the benefits of HI services and striving to enhance their affordability.